Research on Online Non-Contact Test Device and Test Method for Bearing Stiffness of Electric Spindle - Chuanhai Chen; Liang Zhang; Chunlei Hua; Zhifeng Liu; Qingyu Meng; Junze Shi (Machines, 2025)
To enable experimental research on the dynamic support stiffness of electric spindle bearings, the authors designed a magnetic non-contact excitation and test device that can test the support stiffness of electric spindle bearings under a rotating state. The device includes load excitation and displacement detection components, which can collect the load loading and displacement data of electric spindle bearings under machine state in real time. The radial and axial loads can be applied at the same time, and the displacement detection component adopts a high-precision displacement sensor, which can measure the displacement data generated by the electric spindle bearing under the action of the excitation component in real time. A magnetic loading method was proposed for testing the supporting stiffness of the front and rear bearings in electric spindles along the three orthogonal directions of radial X/Y and axial Z. According to the designed device and test method, the dynamic support stiffness of an electric spindle bearing in a vertical machining center is tested, and the variation trend of the bearing support stiffness under the combined action of axial load, radial load and rotational speed is analyzed.